Investigation on Prediction of Life-Threatening Arrhythmia in Long QT Syndrome : A Systematic Review and Meta-Analysis - Lee, Jonathan Vincent; Emmanuela, Mirela; Lee, Jonathan Bryan (Cardiovascular and Cardiometabolic Journal (CCJ), 2025)
Introduction : Use of risk stratification tools in  Long QT Syndrome (LQTS) will be important to direct treatment strategy on each patient and risk of arrhythmia. There are still other factor that could improve the predictive performance of the risk stratification. This study aims to find a new predictor of Life-Threatening Arrhythmia in the LQTS population. Methods : Based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol  (PRISMA) Protocol 2015,  studies  extracted  from  Pubmed, Science Direct, Pubmed Central, EuroPMC, Frontiers with MeSH keywords “Long QT Syndrome AND Predictor AND Life-threatening arrhythmia”. The inclusion criteria were cohort studies in LQTS patients (LQT 1, 2, 3) and the endpoint was life-threatening arrhythmia such as aborted cardiac arrest or sudden cardiac death. Study quality assessed with Newcastle-Ottawa Scale and RevMan 5.4 were used to analyse the data with hazard ratio as the measures. Results : Six  cohort studies  (12.343  subjects)  fulfilled  the  inclusion  criteria. Male <13 years old (HR = 2.73, 95% CI = 1.72-4.33, p = <0.0001) and female >13 years old (HR = 1.81, 95% CI = 1.36-2.41, p = <0.0001) were significant as predictor of life-threatening arrhythmia. Patients with LQT2 (HR = 1.84, 95% CI = 1.36-2.49, p = <0.0001), LQT3 genotype (HR = 3.88, 95% CI = 2.27-6.62, p = <0.00001), and QTc >530 (HR = 2.45, 95% CI = 1.96-3.06, p <0.00001) were also at increased risk of life-threatening arrhythmia.  Syncope occurrence increased the risk (HR = 3.11, 95% CI = 2.47-3.91, p = <0.00001) while beta-blockers usage significantly decreased the risk of life-threatening arrhythmia (HR = 0.46, 95% CI = 0.36-0.60, p = <0.00001). All studies were low risk of bias. Conclusion : There were other predictors of life-threatening arrhythmia in LQTS that might be considered to improve the stratification performance. -- Highlights: 1. In patients with Long QT Syndrome, life-threatening arrhythmia risk is strongly predicted by age-dependent gender differences, prolonged QTc (>530 ms), prior syncope, genotype (LQT2/3), and mitigated by beta-blocker use—offering a sharper edge for clinical risk stratification.